An n-type, new emerging luminescent polybenzodioxane polymer for application in solution-processed green emitting OLEDs1. Issue 11 (21st March 2015) - Gupta, Bipin Kumar; Kedawat, Garima; Kumar, Pawan; Rafiee, Mohammad A.; Tyagi, Priyanka; Srivastava, Ritu; Ajayan, Pulickel M.
<x xml:space="preserve">Abstract</x> An n-type, newly emerging emitter with strong green luminescence and their suitability as electron transport layer for OLEDs devices is demonstrated.